A thermo-responsive chitosan-based injectable hydrogel for delivery of curcumin-loaded polycaprolactone microspheres to articular cartilage: in-vitro and in-vivo assessments - Farnoosh Kalantarnia; Sasan Maleki; Amir Shamloo; Kazem Akbarnataj; Sayed Navid Tavoosi (Carbohydrate Polymer Technologies and Applications)
Articular cartilage has limited regenerative capacity, posing a significant challenge in healing cartilage-related disorders. While injectable hydrogels have shown potential as a treatment, achieving an optimal balance between bio-compatibility, mechanical properties, and drug delivery remains a challenge. This study developed a chitosan-based injectable hydrogel reinforced with bacterial cellulose nanofibers to enhance mechanical stability and biological functionality. The hydrogel exhibited great porosity (∼57.96 %) with a mean pore diameter of ∼104.30 µm, and a compressive modulus of ∼4.65 kPa, offering an encouraging micro-environment for cell proliferation and tissue regeneration. The degradation rate of ∼55 % over 30 days was tailored to match the timeline of cartilage repair. Additionally, polycaprolactone microspheres, prepared by solid/oil/water method, were used to enhance the bio-availability of curcumin and its sustained delivery. The hydrogel system containing drug-loaded microspheres showed ∼23.55 % drug released by day 7. Moreover, anti-bacterial assays confirmed the hydrogel's effectiveness against S. aureus and E. coli. Also, bio-compatibility assessments showed high fibroblast viability over 7 days. In-vivo evaluations on rabbit models indicated significant cartilage regeneration, evidenced by improved locomotion behavior and accelerated cartilage formation with minimized defect boundaries. Similarly, histological analysis revealed enhanced chondrocyte density compared to the control group. These findings highlight the synergistic role of scaffold composition, mechanical properties, and controlled drug delivery in promoting cartilage regeneration, underscoring the potential clinical applications of this multifaceted hydrogel for cartilage repair.